2021
DOI: 10.1089/jpm.2020.0632
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Nursing Competencies Required for Different Levels of Palliative Care Provision: A Qualitative Analysis of Health Care Professionals' Perspectives

Abstract: Background: Nurses must possess adequate competencies to provide high-quality palliative care. Earlier statements have described certain competencies that are relevant for palliative care, yet only limited empirical research has focused on the perspective of healthcare professionals to clarify which competencies are required for different levels of palliative care provision. Objective:The aim was to describe the required palliative nursing competencies of registered nurses aligned to different levels of pallia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 19 publications
5
26
0
2
Order By: Relevance
“…Furthermore, when relating the years of professional experience and having received PC training, nurses with less professional experience reported receiving PC training during their undergraduate education. These results reflect the progressive implementation of palliative care contents in nursing university studies, as recommended by the different scientific societies regarding the need for any nursing professional to receive basic training in palliative care during their undergraduate training [ 20 , 72 , 77 , 79 , 81 , 82 ].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Furthermore, when relating the years of professional experience and having received PC training, nurses with less professional experience reported receiving PC training during their undergraduate education. These results reflect the progressive implementation of palliative care contents in nursing university studies, as recommended by the different scientific societies regarding the need for any nursing professional to receive basic training in palliative care during their undergraduate training [ 20 , 72 , 77 , 79 , 81 , 82 ].…”
Section: Discussionsupporting
confidence: 58%
“…It must be said that these studies have been carried out among nurses who developed their occupations in different workplaces. Some differences can be found among the diverse levels of care despite these deficits being identified globally [ 18 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paramedics also requested for more education in encountering, communication, supporting, and counseling in end-of-life care. Our results are in line with previous studies, which identified supporting the patient and her/his family and carers as a nursing competence required by the professionals working in the basic level of palliative care 2730,37 as well as in palliative paramedicine. 22 The importance of encountering is also highlighted by family members of end-of-life patient as they are shown to emphasize professionalism and compassion of the paramedics’.…”
Section: Discussionsupporting
confidence: 93%
“…46 For this reasons, it has been widely emphasized that nurses need solid cultural competence to meet the distinct needs of patients in palliative care. [47][48][49][50] The responding students also expressed a desire for more education on pharmacological and non-pharmacological pain management. This was supported by low self-assessed levels of competence in nonpharmacological pain management.…”
Section: Discussionmentioning
confidence: 99%